The red blazer girls the mistaken masterpiece - Beil, Michael D. (Alfred A. Knopf, 2011)
Sophie and her friends, who call themselves The Red Blazer Girls, embark on solving a case involving mistaken identities, switched paintings, and some priceless family heirlooms